2014
DOI: 10.1002/dta.1703
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical evaluation of alkaloids in rhizome of Coptis chinensis using laser microdissection and liquid chromatography/mass spectrometry

Abstract: Traditional macroscopic and microscopic identification methods of medicinal materials are economical and practical, but usually experience-based due to few chemical supports. Here histochemical evaluation on bioactive components of Coptidis Rhizoma (CR) in anatomic sections using laser microdissection and liquid chromatography-mass spectrometry (LMD-LC-MS) was developed to correlate the inner quality and outer features of materials from different growing areas. Results of a total 33 peaks representing potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…, MS 2 spectra and B, MS 3 spectra of M1, M2 and M7 [Color figure can be viewed at wileyonlinelibrary.com] groenlandicine 3-O-glucuronide,36,49 while M2 and M7 were deduced to be thalifendine 10-O-glucuronide and berberrubine-9-Oglucuronide,53,54 respectively.M3 and M8 were isomers that eluted at t R = 10.3 min and 11.4 min, respectively (Figure S3, supporting information). They showed the same [M] + ion at m/z 514.1708 (C26 H 28 O 10 N, calculated 514.1708; error, 0.13 ppm) in positive ion mode. The product ion at m/z 338.1401 was observed in their MS/MS spectra corresponding to a loss of 176 Da, which indicated that a GluA unit was attached to the aglycone moiety (Figure S4, supporting information).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…, MS 2 spectra and B, MS 3 spectra of M1, M2 and M7 [Color figure can be viewed at wileyonlinelibrary.com] groenlandicine 3-O-glucuronide,36,49 while M2 and M7 were deduced to be thalifendine 10-O-glucuronide and berberrubine-9-Oglucuronide,53,54 respectively.M3 and M8 were isomers that eluted at t R = 10.3 min and 11.4 min, respectively (Figure S3, supporting information). They showed the same [M] + ion at m/z 514.1708 (C26 H 28 O 10 N, calculated 514.1708; error, 0.13 ppm) in positive ion mode. The product ion at m/z 338.1401 was observed in their MS/MS spectra corresponding to a loss of 176 Da, which indicated that a GluA unit was attached to the aglycone moiety (Figure S4, supporting information).…”
mentioning
confidence: 86%
“…Moreover, Rhizoma coptidis and its isolated alkaloids have been reported to have cardio‐protective and neuro‐protective properties. These properties have been attributed to the presence of bioactive alkaloids within Rhizoma coptidis such as berberine, palmatine and coptisine …”
Section: Introductionmentioning
confidence: 99%
“…The above six protoberberine-type alkaloids (Fig. 2) are considered as the main bioactive compounds of RC [57][58][59][60][61][62][63][64][65]. Moreover, the quantitative determination of berberine and palmatine is a very important index in the quality evaluation of CP.…”
Section: Alkaloidsmentioning
confidence: 99%
“…[7] Some snow lotus healthcare products are even adulterated with other herbs, causing an inevitable concern to public health. [14][15][16] The more we looked into the three medicinal sources, the more we were convinced of the need for an in-depth investigation of the chemical constituents of such raw herbal products as the basis for extending their medical applications [17][18][19] as well as preventing falsification of the products on the market. [8][9][10] Some studies have authenticated different botanical origins of snow lotus medicines by observing macroscopic and microscopic features; [7,11,12] others have preliminarily analyzed chemical components and compared their pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%
“…[5,13] We have also reviewed the literature on the three representative snow lotus herbs with regard to their botany, phytochemistry, and pharmacology, aiming to distinguish the three species from a comprehensive perspective. [14][15][16] The more we looked into the three medicinal sources, the more we were convinced of the need for an in-depth investigation of the chemical constituents of such raw herbal products as the basis for extending their medical applications [17][18][19] as well as preventing falsification of the products on the market. [20] This paper is our attempt to meet this need.…”
Section: Introductionmentioning
confidence: 99%